Overview of West African fisheries under climate change: Impacts, vulnerabilities and adaptive responses of the artisanal and industrial sectors. (September 2016) - Belhabib, Dyhia; Lam, Vicky W.Y.; Cheung, William W.L.
Abstract: Climate change affects ocean conditions, fish stocks and hence fisheries. In West Africa, climate change impacts on fisheries were projected to be mainly negative through multi-facet ways. However, analysis of adaptation responses of fishers to climate change impacts is scarce. This paper reviews the impacts on climate change on fisheries in West Africa and discusses the potential adaptation strategies adopted by both the artisanal and industrial fishing sectors. Overall, climate change and over-exploitation have altered species composition of fisheries catches in West Africa. The effect of ocean warming on fisheries is indicated by the increase in dominance of warmer water species in the landings, shown from an increase in Mean Temperature of Catch, in the region. Climate change induced changes in potential catch and species composition, which inherently have similar symptoms as over-exploitation, are expected to have repercussions on the economic and social performance of fisheries. Both artisanal and industrial sectors may adapt to these changes mainly through expansion of fishing ground that increases operation costs. Our results highlight that historical changes in target species are more common in industrial than artisanal fisheries. This result challenges the prevailing assumption that artisanal fisheries, given their limited movement capacity, would adapt to climate change by shifting target species and/or gear type. Highlights: Climate change is expected to have similar effects as overexploitation in West Africa. Artisanal fishing effort range increases in response to declining catches. Industrial fisheries shift target species/gear type in response to declining catches.